2022
DOI: 10.1021/acs.langmuir.2c00527
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structures of Anionic–Amphoteric Surfactant Mixtures near the Two-Phase Region at Fixed pH

Abstract: We examine the solution structures in a mixed surfactant system of sodium dodecyl sulfate (SDS) and N , N -dimethyldodecylamine N -oxide (DDAO) in water, on both sides of the two-phase boundary, employing dynamic light scattering, small-angle neutron scattering, and Fourier transform infrared spectroscopy. The precipitate phase boundary was accessed by lowering pH to 8, from its floating pH 9.5 value, and was experimentally approached from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…In the case of SDS mixed micelles with dodecyldimethyl amine oxide (C12AO), a study of composition‐dependent changes in various parts of the phase diagram by a combination of FT‐IR, dynamic light scattering and neutron scattering techniques provided additional details on mixed micelle shape and size. Confirmation of an increase in the protonation of the amine oxide in the presence of SDS was also obtained (Tyagi et al, 2022).…”
Section: Applications Of Ft‐ir To Bulk Samples Of Surfactant Aggregatesmentioning
confidence: 71%
“…In the case of SDS mixed micelles with dodecyldimethyl amine oxide (C12AO), a study of composition‐dependent changes in various parts of the phase diagram by a combination of FT‐IR, dynamic light scattering and neutron scattering techniques provided additional details on mixed micelle shape and size. Confirmation of an increase in the protonation of the amine oxide in the presence of SDS was also obtained (Tyagi et al, 2022).…”
Section: Applications Of Ft‐ir To Bulk Samples Of Surfactant Aggregatesmentioning
confidence: 71%
“…Our SANS data expand and complement the findings of Kakitani et al 11 where a higher concentration of 80 mM SDS− DDAO micellar system was found to exhibit near symmetric synergy with DDAO composition, suggestive of twin-tail (gemini) surfactant behavior between SDS and DDAO. Further, work by Prevost et al 12 and Tyagi et al 13 revealed that the precipitation boundary for higher concentrations of this system is symmetric and centered at the equimolar solution. Measurements of the kinematic viscosity of SDS− DDAO solutions by Safonova et al 16 corroborate a transition of the maximum viscosity from 80% to 50% DDAO with increasing total surfactant concentration in the 1−15% w/w range, and here we show that this transition also applies for a range of micellar structural and interaction properties.…”
Section: ■ Conclusionmentioning
confidence: 74%
“…This gave the most self-consistent results and minimized scatter in other fitting parameters at these low concentrations. We also note that our ellipsoidal form factor model is in contrast to previous studies that used a core−shell ellipsoid form factor for this system, 11,13,24 albeit at higher concentrations. However, due to a greater scatter in other fitting parameters obtained from trialling the core−shell model and uncertainty on the SLD of the "shells" (headgroups), as will become evident when regular solution theory results are discussed, we therefore report the SANS data fitted with an ellipsoid form factor and an SLD of −0.691 × 10 −6 Å −2 , corresponding to the surfactant tails.…”
Section: ■ Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Meanwhile, some small spherical particles could be observed, which had similar morphologies to those of the Se-CQDs. The coexistence of monomers (or building blocks) and aggregates is commonly observed in self-assembling systems. However, in the co-assembly of CQDs and the surfactant, the single free CQD theoretically can rarely be seen in the solutions because of electrostatic interaction. It is possible that each CQD is binding to a few molecules of surfactants, whereas these combined surfactant molecules have no visible contribution to the result of DLS and microscopic images.…”
Section: Resultsmentioning
confidence: 99%